ChemInform Abstract: Catalytic Conversion of Alcohols into Carboxylic Acid Salts in Water: Scope, Recycling, and Mechanistic Insights. Issue 45 (October 2016) - Zhang, Lei; Nguyen, Duc Hanh; Raffa, Guillaume; Trivelli, Xavier; Capet, Frederic; Desset, Simon; Paul, Sebastien; Dumeignil, Franck; Gauvin, Regis M.
Abstract: The low to excellent product yield strongly depends on the substrates′ substituents.